Design of distributed implementation and performance analysis of asymptotic optimality for cooperative two-way relaying networks - LI Chun-guo1; ZHONG Chong-xian2; YANG Lv-xi1; PAN Yue3 (Tongxin xuebao)
The realization scheme in the distributed manner was researched for the cooperation transmission of the multi-ple two-way relays,moreover the performance analysis of the asymptotic optimality was also presented.First of all,an upper-bound function was obtained for the true value of the average mean squared error of the whole system by the SNR approximations.Furthermore,a mathematical model was established based on this bound function.Secondly,an optimal solution was obtained for the established problem by using the matrix transform and mathematical derivations.Finally,the realization scheme was obtained in the distributed manner.The proposed scheme avoided the strict requirement that every relay must know the full channel state information（CSI） of the whole networks,while can easily achieve the gain of the relays cooperation by requiring every relay know its local CSI consisted of its forward and backward CSI.There-fore,the proposed scheme not only avoided the central control as required by the central manner and the large amount of the feedback overheads,but also achieved much gain.Theory analysis shows that the proposed scheme is asymptotically optimal.